Dampak Desa Wisata Pulau Pangeran: Impact of Village Tourismof Pulau Pangeran - Jumadi Wuja; Deni Ejar Irmawan (PT Sahabat Investasi Indotama, 2025)
Abstract This study analyzes the impact performance of the Pulau Pangeran Belibak Tourism Village Program, initiated by PT Medco E&P Natuna, using the Social Return on Investment (SROI) method. This program is part of the company's Corporate Social Responsibility (CSR) commitment to improve community living standards. SROI measurement is evaluative, comparing the financial value of impact with the program's investment cost. Results show an average SROI ratio of 4.10 for the 2021-2023 period, meaning every IDR 1 invested yielded IDR 4.10 in benefits, or 410% of the investment value. The program delivered positive impacts to seven key stakeholders: Pokdarwis Management, homestay owners, local MSMEs, pompong boat owners, Belibak villagers, Belibak Village Government, and Medco E&P Natuna. Economic impacts were the largest (51.91%), followed by wellbeing (24.83%) and social impacts (23.26%). The most significant impacts were income generation from tourism activities (21.72%), increased awareness of environmental cleanliness (12.39%), and enhanced community cohesion (10.52%). These findings highlight the potential of community-based tourism village programs as an effective strategy for sustainable regional development. Keywords: Social Return of Investment, Corporate Social Responsibility, village tourism, Medco E&P Natuna, Pulau Pangeran